Double-Layered metamaterial resonator operating at millimetre wave for detection of dengue virus - Qureshi, Suhail Asghar; Zainal Abidin, Zuhairiah; A. Majid, Huda; Ashyap, Adel Y. I.; Chan, Hwang See (Elsevier, 2022)
In this paper, a metamaterial-based resonator is proposed for the detection of dengue infection. The replaceable top layer can measure the dielectric characteristics of blood samples to detect the dengue virus. The sensor observed a shift in the resonant frequency towards higher frequencies with the reduction in the blood’s permittivity. The sensor showed a 0.325 GHz shift in resonance per unit change in the dielectric permittivity. To corroborate the sensor’s practical sensing capability, a sensor prototype was fabricated and validated with alcohol-aqueous solutions. The sensor exhibited shifting of resonance towards lower frequencies with the addition of water contents in methylated alcohol. With the enhanced sensitivity and repeatable measuring capability, the results suggested that this sensor can be applied with real-time applications on the Internet of Medical Things (IoMT) for early remote detection of the dengue outbreak.